The Role of Usage-Based Indices as Indicators of Syntactic Growth in Second Language Writing - Kim, Hyunwoo; Rah, Yangon (Language Research, 2023)
Although syntactic complexity features both length-based syntactic complexity and syntactic sophistication, previous research has predominantly focused on length-based complexity. Against this background, this study aimed to test the validity of syntactic sophistication including usage-based indices in explaining L2 writing proficiency, in comparison to the validity of length-based complexity indices. In a series of multiple regression analyses including various types of indices as predictors of the proficiency levels reflected in 3,201 sample essays, we found that the model including usage-based predictors produced explanatory power comparable to that of the model including length-based indices. However, when we incorporated both usage- and length-based indices in a single regression model, we found that the integrated model had a stronger explanatory power than the length-based and usage-based models, respectively. These results suggest that the proposed usage-based indices can serve as reliable measures of L2 syntactic complexity and may supplement length-based indices.